Many languages, whither literacy? Understanding the ontology of reading in linguistically-diverse contexts - Chong, Su Li (Penerbit Universiti Kebangsaan Malaysia, 2017)
The reading experience of those who are literate in more than one language is highly complex. This makes the reading experience a phenomenon that is not easily understood. Yet, in Malaysia’s education policy, reading goals are subsumed under language learning goals. Such implicit ways of assuming that literacy occurs through language learning not only overlooks any impact language learning may have on literacy practice but also undermines the fact that learning to read in a language is ontologically different from reading through all or any language. This paper discusses a part of an in-depth qualitative study which scrutinized the reading experiences of eight multiliterate Malaysian undergraduates studying in a British university in order to understand the difference between being literate in many languages and choosing to read through any one language. The contrast between multilingual Malaysia and monolingual England formed an important backdrop. In this study, the phenomenological interview and diary-writing were used as research methods to capture the participants’ past reading experience as Malaysian school students and as British university undergraduates. Phenomenographic analysis and discourse analysis were used to analyse the data. Findings from this study suggest that multilingual readers experience “language-ness” because of the specificities of multiple language learning. The phenomenon of language-ness then go on to influence the habituation and sustenance of reading choice across different languages. This paper suggests that as linguistically-diverse countries forge ahead to maintain its citizens’ linguistic abilities, they must not forget that linguistic capital alone cannot shape a nation. Semiotic capital which relates to meaning-making is also critical in shaping an informed nation. This study has important implications towards contemporary discourse about Literacies, language and the reading experience.